Metal-free catalysis based on nitrogen-doped carbon nanomaterials: a photoelectron spectroscopy point of view - Scardamaglia, Mattia; Bittencourt, Carla (Beilstein Journal of Nanotechnology, 2018)
In this review, we discuss the use of doped carbon nanomaterials in catalysis, a subject that is currently intensively studied. The availability of carbon nanotubes since the 1990’s and of graphene ten years later prompted the development of novel nanotechnologies. We review this topic linking fundamental surface science to the field of catalysis giving a timely picture of the state of the art. The main scientific questions that material scientists have addressed in the last decades are described, in particular the enduring debate on the role of the different nitrogen functionalities in the catalytic activity of nitrogen-doped carbon nanotubes and graphene.
Keywords: catalysis; carbon nanotubes; graphene; metal-free; nitrogen doping; photoelectron spectroscopy